2019
DOI: 10.1111/jgh.14841
|View full text |Cite
|
Sign up to set email alerts
|

A framework to support quality of care for patients with chronic intestinal failure requiring home parenteral nutrition

Abstract: Background and Aim Chronic intestinal failure requiring home parenteral nutrition (HPN) is a disabling condition that is best facilitated by a multidisciplinary approach to care. Variation in care has been identified as a key barrier to achieving quality of care for patients on HPN and requires appropriate strategies to help standardize management. Method The Australasian Society for Parenteral and Enteral Nutrition (AuSPEN) assembled a multidisciplinary working group of 15 clinicians to develop a quality fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Seventeen articles comprising guidelines, consensus, recommendation, and position papers were excluded from the ranking process. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] An average of 27 articles (range: 15-53) of the 152 from the primary literature were denoted as most important by individual members of the author group. Five papers from the primary literature were collectively identified (receiving 5 or more votes) as most important by the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen articles comprising guidelines, consensus, recommendation, and position papers were excluded from the ranking process. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] An average of 27 articles (range: 15-53) of the 152 from the primary literature were denoted as most important by individual members of the author group. Five papers from the primary literature were collectively identified (receiving 5 or more votes) as most important by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Alhazzani et al 8 Surviving Sepsis Campaign: Guidelines on the management of critically ill adults with coronavirus disease 2019 (COVID-19) Arvanitakis et al 9 ESPEN guideline on clinical nutrition in acute and chronic pancreatitis Bischoff et al 10 ESPEN guideline on home enteral nutrition Bischoff et al 11 ESPEN practical guideline: Clinical nutrition in liver disease Bischoff et al 12 ESPEN practical guideline: Clinical nutrition in inflammatory bowel disease da Silva et al 13 ASPEN consensus recommendations for refeeding syndrome Gardner et al 14 ACG clinical guideline: Chronic pancreatitis Hardy et al 15 Parenteral provision of micronutrients to pediatric patients: An international expert consensus paper Lal et al 16 Considerations for the management of home parenteral nutrition during the SARS-CoV-2 pandemic: A position paper from the Home Artificial Nutrition and Chronic Intestinal Failure Special Interest Group of ESPEN Lobo et al 17 Perioperative nutrition: Recommendations from the ESPEN expert group Martindale et al 18 Summary of proceedings and expert consensus statements from the international summit "Lipids in parenteral nutrition" Osland et al 19 A framework to support quality of care for patients with chronic intestinal failure requiring home parenteral nutrition Pimental et al 20 ACG clinical guideline: Small intestinal bacterial overgrowth Pironi et al 21 ESPEN guideline on home parenteral nutrition Sheean et al 22 American Society for Parenteral and Enteral Nutrition clinical guidelines: The validity of body composition assessment in clinical populations Tume et al 23 Nutritional support for children during critical illness: European Society of Pediatric and Neonatal Intensive Care (ESPNIC) Metabolism, Endocrine and Nutrition Section position statement and clinical recommendations van der Louw et al 24 Optimal clinical management of children receiving ketogenic parenteral nutrition: A clinical practice guide it requires assessment of volume-weighted percent of fat greater than 5 µm (PFAT 5 ). PFAT 5 must be less than 0.05% to ensure acceptable globule-size distribution within the ILEcontaining formulation, but this was not analyzed in this study.…”
Section: First Author Titlementioning
confidence: 99%
“…Home parental nutrition (HPN) is a basic life-saving treatment that is frequently used in patients with chronic intestinal failure (resulting from benign or malignant diseases) or patients in the late phase of end-stage disease, indicating that it is widely used [14]. Many clinical practice guidelines on patients with HPN have also been published, [72][73][74][75] of which one guideline has been updated twice (2016 and 2020) since it was first published in 2009 (64,73,76). CVC, which is the primary way to deliver HPNs, [64] requires medical staff attention considering the wide use of HPNs.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons behind this high cost are that patients require a specialist and wide-ranging scope of health profes-sionals to address all aspects of care. 18,19 Care is required for patients at home, but there are also high costs associated with initial hospital admission to reach stabilization of medical and surgical care, before a patient can go home, along with training for HPN. As there are no home care PN services for this patient group in Australia, patients are required to be fully self-caring in terms of PN management prior to discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study are similarly reported in a literature review of 21 economic evaluations for HPN, 13 where it was considered overall to be a more expensive treatment but cost‐saving when compared with hospital‐based PN. Reasons behind this high cost are that patients require a specialist and wide‐ranging scope of health professionals to address all aspects of care 18,19 . Care is required for patients at home, but there are also high costs associated with initial hospital admission to reach stabilization of medical and surgical care, before a patient can go home, along with training for HPN.…”
Section: Discussionmentioning
confidence: 99%